Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 67400 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Teucrium rivasii Rigual ex Greuter & Burdet", "TaxonKey is Teucrium scordium subsp. scordioides (Schreb.) Arcang.", "TaxonKey is Celtis australis L.", "TaxonKey is Cistus ladanifer L.", "TaxonKey is Populus alba L.", "TaxonKey is Spergularia fallax Lowe", "TaxonKey is Thymbra capitata (L.) Cav.", "TaxonKey is Arabis planisiliqua (Pers.) Rchb.", "TaxonKey is Hesperis laciniata subsp. laciniata", "TaxonKey is Stipa barbata Desf.", "TaxonKey is Tanacetum annuum L.", "TaxonKey is Lycocarpus fugax (Lag.) O.E.Schulz", "TaxonKey is Arctostaphylos uva-ursi subsp. crassifolia (Braun-Blanq.) Rivas Mart. ex de la Torre, F.Alcaraz & M.B.Crespo", "TaxonKey is Teucrium pugionifolium Pau", "TaxonKey is Arctostaphylos uva-ursi (L.) Spreng.", "TaxonKey is Scrophularia balbisii subsp. valentina (Rouy) Ortega Oliv. & Devesa", "TaxonKey is Scrophularia crithmifolia Boiss.", "TaxonKey is Theligonum cynocrambe L.", "TaxonKey is Erica multiflora Biv.", "TaxonKey is Globularia spinosa L.", "TaxonKey is Agrimonia procera Wallr.", "TaxonKey is Filipendula vulgaris Moench", "TaxonKey is Geum sylvaticum Pourr.", "TaxonKey is Geum urbanum L.", "TaxonKey is Potentilla caulescens L." ] } ] } The dataset includes 67400 records from 93 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0014728-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences